Literasi Budaya Dan Kewarganegaraan Sebagai Pembentukan Karakter Bangsa - Melia Nurkhalisa; Muthia Aprianti; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
With globalization, modernization and digitalization, of course this has a big influence on everything. Apart from the many good influences, there are also quite a few bad influences that are very clear, such as rampant corruption, murders occurring everywhere, brawls between regions, burning of places of worship, weak laws, sexual harassment, robbery, and others. In this research, the author used a research method using the literature study method. The data taken comes from literature sourced from scientific journals in the form of articles, theses, theses, books and from other sources. There are several original characters of the Indonesian nation, including religious, love of the country, mutual cooperation, tolerance, friendliness and creativity. However, with globalization and modernization, this character is slowly fading until efforts are needed to reshape the character of the Indonesian nation.